2019
DOI: 10.7150/thno.32915
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Colorectal Cancer Rewrites Metabolic Program Through a Glut3-YAP-dependent Signaling Circuit

Abstract: Rationale : Cancer cells reprogram cellular metabolism to fulfill their needs for rapid growth and metastasis. However, the mechanism controlling this reprogramming is poorly understood. We searched for upregulated signaling in metastatic colorectal cancer and investigated the mechanism by which Glut3 promotes tumor metastasis. Methods : We compared RNA levels and glycolytic capacity in primary and metastatic colon cancer. The expression and association of Glut3 with clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…Eight weeks later, the mice were sacrificed, all dissected lungs were embedded in paraffin, and tissue sections were stained with hematoxylin and eosin (H&E) and scanned using TissueFax (TissueGnostics). The metastatic burden was calculated as the percentage of the lung area with tumors 16 …”
Section: Methodsmentioning
confidence: 99%
“…Eight weeks later, the mice were sacrificed, all dissected lungs were embedded in paraffin, and tissue sections were stained with hematoxylin and eosin (H&E) and scanned using TissueFax (TissueGnostics). The metastatic burden was calculated as the percentage of the lung area with tumors 16 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, both GLUT1 and GLUT3 have been up-regulated in poorly differentiated endometrial and breast cancers, both at mRNA and protein levels [75]. Transactivation of GLUT3 occurs in a Yes-associated protein (YAP)-dependent manner, suggesting that this pathway serves as a regulator of metabolic reprogramming during cancer progression, and thus can be considered as a promising anti-cancer therapeutic target [76].…”
Section: Interplay Between Hif-1 and Facilitative Glucose Transportersmentioning
confidence: 99%
“…It has been reported that tyrosine 105-phosphorylated PKM2, which is induced by several tyrosine kinases, reduces LATS1 protein stability and downregulates it, thereby activating YAP (125). Furthermore, another report has shown that PKM2 directly interacts with YAP and enhances YAP transcriptional activity (126).…”
Section: The Role Of Yap/taz In Glucose Metabolismmentioning
confidence: 99%